Kinematic gait analysis of a young man after amputation of the toes - Forczek Wanda; Ruchlewicz Tadeusz; Gawęda Anna (Sciendo, 2014)
Study aim: the foot is recognised as a "functional unit" with two important aims: to support body weight and to serve as a lever to propel the body forward. When it is impaired, the locomotor pattern has to adapt to compensate for the dysfunction. The purpose of this study was to investigate gait kinematics of a man after bilateral partial amputation of the toes.